Selenium inhibits ferroptosis in hyperglycemic cerebral ischemia/reperfusion injury by stimulating the Hippo pathway. - Lu Li; Meng Wang; Yan-Mei Ma; Lan Yang; Deng-Hai Zhang; Feng-Ying Guo; Li Jing; Jian-Zhong Zhang (PLoS ONE, 2023)
Hyperglycemia can exacerbate cerebral ischemia/reperfusion (I/R) injury, and the mechanism involves oxidative stress, apoptosis, autophagy and mitochondrial function. Our previous research showed that selenium (Se) could alleviate this injury. The aim of this study was to examine how selenium alleviates hyperglycemia-mediated exacerbation of cerebral I/R injury by regulating ferroptosis. Middle cerebral artery occlusion (MCAO) and reperfusion models were established in rats under hyperglycemic conditions. An in vitro model of hyperglycemic cerebral I/R injury was created with oxygen-glucose deprivation and reoxygenation (OGD/R) and high glucose was employed. The results showed that hyperglycemia exacerbated cerebral I/R injury, and sodium selenite pretreatment decreased infarct volume, edema and neuronal damage in the cortical penumbra. Moreover, sodium selenite pretreatment increased the survival rate of HT22 cells under OGD/R and high glucose conditions. Pretreatment with sodium selenite reduced the hyperglycemia mediated enhancement of ferroptosis. Furthermore, we observed that pretreatment with sodium selenite increased YAP and TAZ levels in the cytoplasm while decreasing YAP and TAZ levels in the nucleus. The Hippo pathway inhibitor XMU-MP-1 eliminated the inhibitory effect of sodium selenite on ferroptosis. The findings suggest that pretreatment with sodium selenite can regulate ferroptosis by activating the Hippo pathway, and minimize hyperglycemia-mediated exacerbation of cerebral I/R injury.